GERAK DASAR LOKOMOTOR, NON LOKOMOTOR, DAN MANIPULATIF DALAM PERMAINAN BOLA KASTI PADA SISWA KELAS V SDN SIDOMULYO KECAMATAN SEMEN KABUPATEN KEDIRI TAHUN PEMBELAJARAN 2025 - Muhammad Zainul Muttaqin (JURNAL ILMIAH NUSANTARA, 2025)
This study aimed to examine the effectiveness of a modified learning model for the game of rounders (bola kasti) using soft balls and adapted bats referred to as kasbol in improving student learning outcomes. The central research question was whether this kasbol-based approach could enhance the performance of fifth-grade students at SD Negeri Sidomulyo, Kecamatan Semen, during the 2025 academic year.The research employed a Classroom Action Research (CAR) design, conducted over two cycles, each consisting of planning,implementation, observation, and reflection phases. A mixed-method approach combining qualitative and quantitative data was used. The study involved 23 students (12 boys and 11 girls) and was carried out between April and May 2025.Data collection instruments included observation sheets for lesson implementation, student motivation and interest, student response questionnaires, and practical performance tests. Data were analyzed descriptively and quantitatively using predetermined formulas.Findings revealed a positive impact of the kasbol learning model. Student achievement improved from 75.2% in Cycle I to 79.4% in Cycle II, while mastery learning increased significantly from 73.9% to 96%. These results indicate that the modified game approach effectively boosted student engagement and performance.Based on these findings, it is recommended that teachers continue enhancing their instructional skills, adopt innovative methods, and consider implementing kasbol in physical education. Students are encouraged to actively participate in lessons and overcome hesitation when engaging in modified sports activities.